1991
DOI: 10.1161/01.cir.83.3.836
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen, viscosity, and white blood cell count are major risk factors for ischemic heart disease. The Caerphilly and Speedwell collaborative heart disease studies.

Abstract: Methods and Results. The two studies have a common core protocol and are based on a combined cohort of 4,860 middle-aged men from the general population. The first follow-up was at a nearly constant interval of 5.1 years in Caerphilly and 3.2 years in Speedwell; 251 major IHD events had occurred. Age-adjusted relative odds of IHD for men in the top 20% of the distribution compared with the bottom 20% were 4.1 (95% confidence interval, 2.6-6.5) for fibrinogen, 4.5 (95% confidence interval, 2.8-7.4) for viscosit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

30
382
5
20

Year Published

1991
1991
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 897 publications
(437 citation statements)
references
References 24 publications
30
382
5
20
Order By: Relevance
“…1,2 In other studies, high plasma viscosity was shown to lead to an increased risk of acute MI in patients with unstable angina pectoris. 3,4 Furthermore, a relationship of an early increase in plasma viscosity during acute MI and reinfarction or death was shown.…”
mentioning
confidence: 93%
“…1,2 In other studies, high plasma viscosity was shown to lead to an increased risk of acute MI in patients with unstable angina pectoris. 3,4 Furthermore, a relationship of an early increase in plasma viscosity during acute MI and reinfarction or death was shown.…”
mentioning
confidence: 93%
“…Previous reports from the prospective Caerphilly Study have shown that circulating inflammatory markers including fibrinogen, plasma viscosity and leucocyte count [2,3]; C-reactive protein (CRP) [4]; and ␣1-antitrypsin and ␣2-macroglobulin [5] are associated with CHD risk. These results are consistent with recent meta-analyses of data from several prospective studies (including Caerphilly) for fibrinogen [6], plasma viscosity [7], leucocyte count [8] and CRP [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The aims of the present study were therefore to examine the associations of IL-6 with CHD and IS events, and to estimate the effect of these on the associations of several "downstream" inflammatory markers with CHD and IS, which were updated from our previous reports [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] However, for many years, fibrinogen has been recognized as an important risk factor for cardiovascular events and several prospective epidemiological studies have documented an association between fibrinogen and future cardiovascular diseases, which is not substantially modified after multivariate adjustment for other risk factors. [12][13][14][15] The metabolic background of this strong relationship between fibrinogen levels and cardiovascular risk has not been fully elucidated, although a number of studies showed significant associations between fibrinogen and several other cardiovascular and hemostatic variables. [16][17][18][19][20][21][22][23] Unfortunately, measurements for fibrinogen were poorly standardized for some time, thereby limiting its wide adoption in the clinical setting.…”
mentioning
confidence: 99%